2013
DOI: 10.1155/2013/526512
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Retraction of Bowel by Intraluminal Injectable Cyanoacrylate-Based Magnetic Glue

Abstract: Magnetic retraction offers advantages over physical retraction by graspers because of reduced tissue trauma. The objectives of this study are to investigate a novel method of magnetisation of bowel segments by intraluminal injection of magnetic glue and to demonstrate the feasibility of magnetic retraction of bowel with sufficient force during minimal access surgery. Following an initial materials characterisation study, selected microparticles of stainless steel (SS410-μPs) were mixed with chosen cyanoacrylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
(41 reference statements)
1
4
0
Order By: Relevance
“…1c. The morphologies and magnetisation curves for the commercial stainless steel microparticles were reported earlier elsewhere [13]. As expected, the curves are symmetric and the magnetisation at saturation, Ms, can be deduced from the plateau, when the magnetisation does not increase any more with the magnetic field.…”
Section: Characterisation Of Magnetic Particlessupporting
confidence: 72%
See 1 more Smart Citation
“…1c. The morphologies and magnetisation curves for the commercial stainless steel microparticles were reported earlier elsewhere [13]. As expected, the curves are symmetric and the magnetisation at saturation, Ms, can be deduced from the plateau, when the magnetisation does not increase any more with the magnetic field.…”
Section: Characterisation Of Magnetic Particlessupporting
confidence: 72%
“…The probe applies initial suction through small suction holes at its distal end before its long needle (19-gauge) is inserted, via a central channel of the probe, into the lumen of the bowel for injection of ferrofluid in large volume. More detailed illustration of our proposed transperitoneal injection can be found from our recently published glue-based magnetic fluid for bowel magnetisation and retraction [13]. This design facilitates intraluminal injection without the need for use of additional graspers.…”
Section: Preparation Of Magnetic Ferrofluids For Intra-luminal Bowel mentioning
confidence: 99%
“…In particular, the ceramic bioglass greatly promoted coagulation and exhibited remarkable adhesive properties. Wang et al prepared a magnetic adhesive from steel microparticles and a cyanoacrylate adhesive (Loctite 4014) [ 608 ]. Intraluminal injection of the magnetic adhesive into ex vivo porcine colonic segments and a magnet at the injection site resulted in polymerization of an intraluminal, mucosally adherent coagulum that allows adequate retraction of the bowel with little tissue trauma during minimally invasive surgery.…”
Section: Other Soft Tissue Regeneration and Engineeringmentioning
confidence: 99%
“…An interesting solution for magnetic retraction of bowel by intraluminal injectable cyanoacrylate-based magnetic glue has been proposed by Wang et al [13]. Results showed that with an injected volume of 2 ml and with a particle concentration of 1 g/ml, the technique produced maximal magnetic retraction forces of 2.24 ± 0.23 N and 5.11 ± 0.34 N, with use of 5 and 10 mm probes, respectively [13].…”
Section: Magnetically Driven Medical Devicesmentioning
confidence: 99%